Integrasi PjBL dan Media Podcast sebagai Inovasi Pembelajaran Bahasa Arab di Madrasah Tsanawiyyah - Aisyah, Farah Azzahratu; Zahro, Aminatus (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: To address the low speaking proficiency (maharah kalam) of Madrasah Tsanawiyyah students caused by conventional teaching methods by offering a pedagogical innovation through the integration of the Project-Based Learning (PjBL) model and educational podcasts. Methodology/approach: This study employs a systematic literature review method to synthesize and formulate the implementation steps of the instructional design. Findings: The PjBL-Podcast integration is effective in increasing students' active involvement, self-confidence, and speaking fluency. The learning stages include determining contextual topics, group management, collaborative scriptwriting, and digital publication. Practical implications: This study offers a strategic and practical solution for developing an Arabic language curriculum that is adaptive to the digital era, while simultaneously overcoming technical challenges and the heterogeneity of students' abilities in madrasahs. Originality/value: Unlike previous studies, this research positions podcasts not merely as an auditory teaching aid, but as an authentic project product that requires students to independently conduct investigations, collaborate, and produce language.